2000
DOI: 10.1016/s0015-0282(00)01594-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after quinacrine sterilization in Vietnam. Part II: interim safety analysis

Abstract: Ectopic pregnancies do not appear to be increased compared with U.S. surgical sterilization rates. The data on other adverse events are more difficult to interpret.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We have shown that a single treatment with 5% polidocanol foam results in a permanent collagen occlusion of the intramural Fallopian tube in non-human primates (7,8) and female baboons successfully treated do not become pregnant (9). However, not all females treated with polidocanol foam develop bilateral occlusion after a single treatment as is the case with quinacrine sterilization (3). A functional occlusion of the proximal tube that prevents movement of the active agent into the intramural Fallopian tube could explain some cases of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that a single treatment with 5% polidocanol foam results in a permanent collagen occlusion of the intramural Fallopian tube in non-human primates (7,8) and female baboons successfully treated do not become pregnant (9). However, not all females treated with polidocanol foam develop bilateral occlusion after a single treatment as is the case with quinacrine sterilization (3). A functional occlusion of the proximal tube that prevents movement of the active agent into the intramural Fallopian tube could explain some cases of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Quinacrine sterilization, typically performed in the follicular phase has a failure of about 27% with one application (3). Timing might also explain some cases of unilateral or bilateral failed microinsert placement during hysteroscopic permanent contraception (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insufficient family planning is the leading cause of maternal mortality in developing countries. 18 In this study there was endometrial hyperplasia in two (0.37%) and endometrial carcinoma in 2(0.37%) after quinacrine sterilization. In an international study the women were investigated for endometrial abnormalities through transvaginal ultrasound and subsequent histopathology for confirmation and it was found that the chances of histopathological evidence of endometrial abnormalities were increased if history of irregular bleeding was present along with abnormal endometrium on ultrasound.…”
Section: Discussionmentioning
confidence: 48%
“…Subsequent research sought the best dose, the optimum number of quinacrine applications, and possible adjuvants to enhance efficacy (4)(5)(6)(7)(8). Today, quinacrine when used for sterilization is given in the form of slow-releasing pellets to avoid rapid absorption of the drug (9).…”
mentioning
confidence: 99%